Circular Model of Some on Instagram Social Media in Improving the Corporate Image of Cozy Coffee & Eatery - Iing Saefudin; Amin, Amin; Amron Maroghi Ash; Elfarras Az Zahra (Sean Institute, 2025)
This study aims to analyze the application of the Circular Model of Some and Types on Instagram to enhance the corporate image of Cozy Coffee & Eatery. In the digital era, social media has become an important tool for companies to build communication and relationships with the public. This study used a qualitative method with a descriptive approach, using data collection techniques such as observation, interviews, and documentation of the activities of the @cozy_caffeandeatery Instagram account. The results indicate that the application of the Circular Model of Some, which includes the aspects of Share, Optimize, Manage, and Engage, has been effective. In the Share aspect, the account is able to convey information and messages efficiently to the public. In the Optimize aspect, the use of hashtags and collaboration with influencers helps expand reach and strengthen promotional strategies. The Manage aspect demonstrates consistent content management through uploads of feeds, reels, and promotional videos. Meanwhile, the Engage aspect reflects active interaction with the audience through comment replies, giveaways, and promotional programs that increase customer engagement. Overall, the application of the Circular Model of Some and Types on the @cozy_caffeandeatery Instagram account has proven effective in building a positive image, increasing engagement, and strengthening brand identity among the public.